On the Solution of the Linear Set-valued Homogeneous Cauchy Problem with the Hukuhara Derivative - Plotnikov, Andrej (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The paper considers a linear set-valued homogeneous Cauchy problem with the Hukuhara derivative and provides its analytical solution. У статті розглядається лінійна однорідна задача Коші з багатозначними значеннями та похідною Хукухари та надається її аналітичний розв'язок.